2012
DOI: 10.1002/adsc.201200314
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed and Hybrid Acids‐Assisted Synthesis of [60]Fulleroazepines in One Pot under Mild Conditions: Annulation of N‐Sulfonyl‐2‐aminobiaryls with [60]Fullerene through Sequential C‐H Bond Activation, C‐C and C‐N Bond Formation

Abstract: An extraordinarily efficient hybrid acidsassisted, palladium-catalyzed and chelating-group-assisted C À H bond activation of N-sulfonyl-2-aminobiaryls and their annulations with [60]fullerene via sequential C À C and C À N bond formation at room temperature to afford [60]fulleroazepines is demonstrated. The formation of [60]fulleroazepines is highly regioselective and tolerant to both electronwithdrawing and electron-donating groups on the aryl moiety and the reaction gives monofunctionalized fullerenes in goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 110 publications
2
20
0
Order By: Relevance
“…The consecutive C−H bond activation and alkyne insertion process is considerably more complex as it may involve dissociative cleavage of the Pd−N bond in the first alkyne‐inserted intermediate ( IA ), formation of a relatively less common and unstable eight‐membered palladacycle ( IB ), and competing coordination with another resting directing group (NHAc) in intermediate IC ; this may be followed by second competing C−H bond activation (C‐6–H versus C‐3′–H, Scheme e). Our research group has demonstrated palladium‐catalyzed C‐2′–H activation of N ‐tosyl‐2‐aminobiaryls followed by the insertion of [60]fullerene and CO to yield fullerobenzoazepines and phenanthridinones, respectively. The activation of C‐2′–H is considerably sensitive to the substitution on the nitrogen of 2‐aminobiaryls, which has engendered a demand for developing another new condition for C‐2′–H activation by using other N ‐substituted 2‐aminobiaryls.…”
Section: Methodsmentioning
confidence: 99%
“…The consecutive C−H bond activation and alkyne insertion process is considerably more complex as it may involve dissociative cleavage of the Pd−N bond in the first alkyne‐inserted intermediate ( IA ), formation of a relatively less common and unstable eight‐membered palladacycle ( IB ), and competing coordination with another resting directing group (NHAc) in intermediate IC ; this may be followed by second competing C−H bond activation (C‐6–H versus C‐3′–H, Scheme e). Our research group has demonstrated palladium‐catalyzed C‐2′–H activation of N ‐tosyl‐2‐aminobiaryls followed by the insertion of [60]fullerene and CO to yield fullerobenzoazepines and phenanthridinones, respectively. The activation of C‐2′–H is considerably sensitive to the substitution on the nitrogen of 2‐aminobiaryls, which has engendered a demand for developing another new condition for C‐2′–H activation by using other N ‐substituted 2‐aminobiaryls.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we successfully introduced the palladium‐catalyzed CH activation strategy into fullerene chemistry, and synthesized a series of novel [60]fullerene derivatives 3. The CH activation/CN cyclization strategy has been successfully applied to heteroannulations of C 60 with various anilides,3a N ‐benzylsulfonamides,3d N ‐substituted benzamides,3b N ‐sulfonyl‐2‐aminobiaryls,4 and N ‐(2‐arylethyl)sulfonamides,3f affording C 60 ‐fused indolines, tetrahydroisoquinolines, isoquinolinones, azepines, and tetrahydrobenzazepines, respectively. The CH activation/CO cyclization strategy has been successfully applied to heteroannulations of C 60 with various arylsulfonic acids3c and phenylethyl/benzyl alcohols,3e affording C 60 ‐fused sultones, tetrahydrobenzoxepines and isochromans, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As the formation of C 60 -fused seven-membered-ring compounds through Pd-catalyzed C-H bond activation presumably proceeds through a relatively scarce eight-membered palladacycle intermediate, the synthesis of C 60 -fused seven-membered-ring compounds remains a great challenge. 8e, 9 In continuation of our Pd-catalyzed reactions of C 60 , 8 herein we report a novel heteroannulation of C 60 with various N-(2-arylethyl) sulfonamides to give the rare C 60 -fused tetrahydrobenzazepines through a Pd-catalyzed C-H activation protocol. Furthermore, these C 60 -fused tetrahydrobenzazepines were found to undergo TfOH-promoted rearrangements.…”
mentioning
confidence: 96%
“…However, this protocol is relatively underdeveloped and limited to a few Pd-catalyzed heteroannulations of C 60 with anilides, 8a benzamides, 8b arylsulfonic acids, 8c N-benzyl sulfonamides, 8d phenylethyl/benzyl alcohols 8e and N-sulfonyl-2-aminobiaryls. 9 Therefore, there is still a demand to prepare more fullerene compounds with different appended moieties through Pd-catalyzed C-H bond activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation